Account of the Martyrs in the Provinces of La Florida - Ore, Luis Jerónimo de, 1554-1630 (Book collections on Project MUSE., 2017)
This edition of Luis Jerónimo de Ore's work presents readers with a new introduction and an annotated translation that place the text in the broader context of international politics.